Frequency dependence of impedances at the acupuncture point Quze (PC3). - Johng, H.M.
Investigates an equivalence circuit model for characterizing a person's electrical properties. It is not straightforward to compare skin-impedance data of various research groups because the impedance depends very sensitively on measurement conditions such as the shape, size, material, and contact pressure of the electrodes, the skin humidity due to sweat, the applied current, the shape of the wave, and even the psychological condition of the subject. With these subtleties in mind, we show the impedance data taken by various groups and our data (shown with curves). Data of other groups are scattered around our curve.
Keywords: PC3.; Acupuncture point Quze; Applied current; Equivalence circuit model; Impedance data; Pericardium; Person's electrical properties characterization; Skin humidity; Subject psychological condition; Sweat; Traditional Chinese medicine; Wave shape